BENEFITS OF ELDERLY EXERCISE IN IMPROVING ELDERLY FITNESS IN WAKARLELI VILLAGE SOUTHWEST MALUKU DISTRICT, IN 2021 - Isidorus Jehaman; Naniyawati Sarlota; Sabirin Berampu; Raynald Ignasius Ginting; Redi Tantangan; Timbul Siahaan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2022)
Technological developments affect a person's life. One of the signs is the level of public health, life expectancy is getting longer, so the number of elderly residents will increase. The growth of the world's population aged over 60 years exceeds 7% of the total population. Indonesia is one of the countries with very rapid growth of the elderly population due to low mortality and birth rates. Problems that often arise in the elderly are fitness problems so that they are disturbed in carrying out daily activities. Interventions that can be given to help overcome the fitness of the elderly are elderly gymnastics. This activity was carried out with the aim of knowing the benefits of exercise in improving the fitness of the elderly. The intervention method used to overcome the fitness of the elderly is to offer elderly arts. The elderly exercise given is very useful to maintain and maintain conditions to stay fit and maintain physiological physical properties such as elasticity, contractility, and endurance. This activity is given to the elderly in Wakarleli Village, Southwest Maluku Regency in 2021. The measuring instrument used to measure the elderly's fitness is using arm curls. Respondents who took part in this activity numbered 11 people with an average age of over 60 years. After doing elderly exercise for 6 (six) times, p is 0.003 smaller than 0.05 (0.003 <0.05), which means that elderly exercise can improve the fitness of the elderly in Wakarleli Village in 2021.